2011
DOI: 10.1002/chem.201100253
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of the {Fe(NO)2}9 Dinitrosyl Iron Complexes (DNICs) into S‐Nitrosothiols (RSNOs) Triggered by Acid–Base Pairs

Abstract: S-nitrosation of the coordinated thiolate of dinitrosyl iron complexes (DNICs) to generate S-nitrosothiols (RSNOs) was demonstrated. Transformation of [{(NO)(2)Fe(μ-StBu)}(2)] (1-tBuS) into the {Fe(NO)(2)}(9) DNIC [(NO)(2)Fe(StBu)(MeIm)] (2-MeIm) occurs under addition of 20 equiv of 1-methylimidazole (MeIm) into a solution of 1-tBuS in THF. The dynamic interconversion between {Fe(NO)(2)}(9) [(NO)(2)Fe(S-NAP)(dmso)] (2-dmso) (NAP = N-acetyl-D-penicillamine) and [{(NO)(2)Fe(μ-S-NAP)}(2)] (1-NAP) was also observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 71 publications
0
21
1
Order By: Relevance
“…As an alternative, it has also been proposed that DNIC are in equilibrium with Fe(II), NO, thiolate, and S-nitrosothiol [1, 10]. Our observations do not support either hypothesis, but at least partially support the work of Tsou and Liaw [29] who showed that one, but not two, thiol-containing DNIC can produce S-nitrosothiol, but only under acidic conditions. These authors did not consider that this could occur through the intermediacy of nitrite/nitrous acid.…”
Section: Discussioncontrasting
confidence: 75%
“…As an alternative, it has also been proposed that DNIC are in equilibrium with Fe(II), NO, thiolate, and S-nitrosothiol [1, 10]. Our observations do not support either hypothesis, but at least partially support the work of Tsou and Liaw [29] who showed that one, but not two, thiol-containing DNIC can produce S-nitrosothiol, but only under acidic conditions. These authors did not consider that this could occur through the intermediacy of nitrite/nitrous acid.…”
Section: Discussioncontrasting
confidence: 75%
“…Several examples of DNICs have been experimentally isolated and studied and includes the more common cysteine‐bound (S‐bound) DNICs and the rarer N‐bound, O‐bound DNICs . {Fe(NO) 2 } 9 or {Fe(NO) 2 } 10 have also been shown to interconvert into each other via a reversible redox reaction . The formation of DNICs from the action of NO in biological systems has been reported by experimental studies for both non‐heme iron species and heme iron species .…”
Section: Introductionmentioning
confidence: 99%
“…In their opinion, it must be defined as d 9 ({Fe(NO) 2 } 9 in the Feltham-Enemark presentation) [9][10][11][12][13]. As regards the nature of DNIC responsible for the EPR signal at g aver.…”
Section: Introductionmentioning
confidence: 99%